Analisis Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Jasa Pengiriman Cargo di PT. Andalas Wahana Rezeki (AWR) Bukittinggi - Widia Sri Fahdila; Septria Susanti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This research is motivated by the number of customers experiencing fluctuations, which indicates a potential issue with customer satisfaction levels. This condition is suspected to be related to suboptimal service quality as well as customer assessment of prices compared to other shipping service providers. Therefore, this research aims to examine the extent to which service quality and price affect customer satisfaction regarding cargo delivery services at PT. Andalas Wahana Rezeki (AWR) Bukittinggi. This research uses a quantitative approach involving 99 respondents as samples. Information was collected by distributing questionnaires (Google Form). The data were analyzed using SPSS version 31. The data analysis techniques included testing validity and reliability, classical assumption tests consisting of tests for normality, multicollinearity, and heteroscedasticity, multiple linear regression analysis, hypothesis testing through partial and simultaneous tests, as well as testing the coefficient of determination (R²). The findings indicate that both service quality and pricing are key drivers of customer satisfaction, meaning customers evaluate not only what they receive but also what they pay for it. High service quality builds trust, comfort, and positive experiences, while appropriate pricing reinforces perceptions of fairness and value. When combined, these factors strengthen overall satisfaction and likely influence loyalty and repeat behavior. The implication for companies is the need to consistently deliver reliable, responsive service while aligning pricing strategies with customer expectations and perceived benefits. Failing to balance these elements may weaken satisfaction, even if one factor performs well independently.